Die litauischen und lettischen Arbeitslieder Ein Vergleich - Huelmann, Magdalene (Slavistische Beitraege, 1996)
For the present work 909 Lithuanian and 5,670 Latvian song types were examined. In the Latvian and Lithuanian folklore, songs about plowing, hay and grain harvesting, harvesting and further processing of flax and hemp, livestock herding, milling, as well as the number of small lieers, belong to the overall body of working songs in Latvian and Lithuanian folklore spinning, weaving and washing and finally some songs about hunting and fishing.